A promising strategy for designing reduced-fat model meat emulsions by utilization of pea protein-agar agar gel complex. (July 2021) - Öztürk-Kerimoğlu, Burcu
Graphical abstract: Highlights: Beef fat was substituted by pea protein-agar agar gel in emulsified beef systems. The gel complex reduced total fat and caloric values while it increased protein. Increased concentrations of the gel resulted in higher stability and cook yield. Microstructure, color and texture were considerably affected by gel inclusion. Thermograms gave promising data for oxidation in gel containing emulsions. Abstract: Designing low-fat formulations is of high interest to obtain healthier meat products. Considering the potential techno-functional impacts of protein-polysaccharide gels, the current research aimed to examine the utilization of a gel system that comprised pea protein and agar agar (PAG) to partially (30 % or 70 %) or totally (100 %) replace fat in model meat emulsions. The inclusion of PAG decreased total fat and energy content while it yielded increased moisture, protein, and dietary fiber contents. Both emulsion stability as well as cook yield increased by incorporation of higher levels of PAG. Lightness and yellowness increased while redness decreased in samples formulated with PAG regardless of the addition level. Total replacement of fat with PAG gave softer but more adhesive texture. Microscopic images of the emulsions containing PAG confirmed the interconnections between gel and meat matrix. The incorporation of PAG was effective to increase oxidation onset temperature determined by DSC curves. Overall, the findings pointed out the favorable effects of PAG with increased functional and chemical properties as well as nutritive value of model meat emulsions, indicating the possibility to be incorporated into further processed meat products.